The Pedagogy of Secondary-School Mathematics - Zhang, Shizao (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
Congratulations on the publishing of this book! The Chinese version of this book has received excellent reviews at multiple international book fairs, and it demonstrates the Chinese characteristics in the process of discipline construction." - Gang Tian, Yiming Cao, and Lianghuo Fan This book elucidates the principal aspects and characteristics of secondary school mathematics teaching and learning in China. It combines the cultivation of students' mathematical abilities with the improvement of teaching skills, and explores from both theory and practice to create mathematical pedagogy which has been widely recognized by experts in this field. This book presents a number of mathematics teaching principles and methods, and has been used as an important resource book for mathematics teachers' education.
Introduction -- Chapter 1 Logic in Secondary-School Mathematics -- Chapter 2 Thinking in Secondary-School Mathematics -- Chapter 3 Methods in Secondary-School Mathematics -- Chapter 4 Mathematical Abilities in Secondary School -- Chapter 5 Math Learning in Secondary School -- Chapter 6 Curriculum Standards of Secondary-School Mathematics -- Chapter 7 Teaching Modes and Means of Secondary-School Mathematics -- Chapter 8 Teaching Principles and Methods of Secondary-School Mathematics -- Chapter 9 Teaching of Mathematics in Secondary School -- Chapter 10 Research on Teaching of Secondary-school Mathematics -- Chapter 11 Measurements of Secondary-school Mathematics Education -- Chapter 12 Research on and Practice of Secondary-school Mathematics Education -- Appendix.
Keywords: Mathematics; Educational psychology; Mathematics Education; Mathematical Teaching Educational Skills; Educational Psychology